A Study Of Interaction Of Dicresyl Monothiophosphate With Noble Metals By Electrochemical And Spectroscopic Methods - D. R. Nagaraj (Society for Mining, Metallurgy & Exploration, 1991)
There are few organic ligands that can adsorb effectively on noble metals, especially gold, in aqueous media. Ligands containing sulfur and nitrogen donors are known to be the most effective. Dithiophosphorous acids, for example, are known to adsorb on gold under certain conditions and these, along with xanthates, are used traditionally to recover gold values by flotation from ores. These compounds, however, are not necessarily selective for gold since most of the associated sulfide minerals are also floated. Monothiophosphorous acids, on the other hand, were recently discovered to float gold values selectively from sulfide-containing ores in a mildly alkaline medium; thus the dicresyl monothiophosphate is now used commercially in a gold flotation operation in the U.S.